2010
DOI: 10.3791/1894
|View full text |Cite
|
Sign up to set email alerts
|

Vascular Occlusion Training for Inclusion Body Myositis: A Novel Therapeutic Approach

Abstract: Inclusion body myositis (IBM) is a rare idiopathic inflammatory myopathy. It is known to produces remarkable muscle weakness and to greatly compromise function and quality of life. Moreover, clinical practice suggests that, unlike other inflammatory myopathies, the majority of IBM patients are not responsive to treatment with immunosuppressive or immunomodulatory drugs to counteract disease progression 1 . Additionally, conventional resistance training programs have been proven ineffective in restoring muscle … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0
2

Year Published

2012
2012
2019
2019

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 36 publications
(29 citation statements)
references
References 5 publications
1
26
0
2
Order By: Relevance
“…Using elastic bands, Wilson, et al [27] observed a significant elevation in the determinants of hypertrophy without identifying significant elevations in the indicators of muscle damage (muscle soreness, muscle swelling and power) up to 24 h post-exercise. This supports the idea of using BFR resistance exercise as an effective alternative for promoting significant enhancements in the levels of strength and hypertrophy for those who are unable to train at high loads [28,29]. It also supports the relative safety of this method of training [30].…”
Section: Aop Pressuressupporting
confidence: 61%
“…Using elastic bands, Wilson, et al [27] observed a significant elevation in the determinants of hypertrophy without identifying significant elevations in the indicators of muscle damage (muscle soreness, muscle swelling and power) up to 24 h post-exercise. This supports the idea of using BFR resistance exercise as an effective alternative for promoting significant enhancements in the levels of strength and hypertrophy for those who are unable to train at high loads [28,29]. It also supports the relative safety of this method of training [30].…”
Section: Aop Pressuressupporting
confidence: 61%
“…In order to assess the expression of genes related to MSTN signalling, muscle samples previously obtained from an IBM patient who underwent a 12-week BFRRT programme were utilized [9, 10]. BFRRT was chosen because this training mode is effective in increasing muscle mass while using low exercise loads [14].…”
Section: Methodsmentioning
confidence: 99%
“…In animal models, despite the limitations of the RE models and protocols, some studies have also observed attenuation of muscle atrophy under catabolic conditions such as muscle disuse [12][13][14][15][16]. Furthermore, we recently demonstrated in a case report that chronic RE with vascular occlusion attenuated the loss of skeletal muscle functionality (strength) in a subject with body inclusion myositis [17]. RE also promotes the therapeutic role of glucose homeostasis, because mechanical stimuli are widely known to improve glucose uptake to skeletal muscle through glucose transporter-4 (GLUT4) translocation to the sarcolemma [18].…”
Section: Introductionmentioning
confidence: 92%